PENDEKATAN KOMUNIKASI ORGANISASI DALAM PENYAMPAIAN KEBIJAKAN KANTIN BEBAS 5P (PEWARNA, PENYEDAP, PEMANIS, PENGAWET DAN PERASA) DI SMP NEGERI 7 SURABAYA - Mohammad Insan Romadhan (Jurnal Riset Komunikasi (JURKOM), 2018)
Policy is always there in every organization, the policy is the basic guidelines of the process of the passage of an organization, so that the organization can run properly. Based on the foregoing researchers interested in examining the implementation of the Organization's communications approach undertaken in delivering a policy that canteen is free of 5P to the owner of the canteen in 7th junior high school. This type of descriptive research, the informant is a headmaster and owner. The technic of collecting data using interviews, observation and documentation of the data analysis techniques, researchers using the technique of data analysis from Creswell. Results of research i.e. organizational communication approach applied by the head of the7th junior school in surabaya in the delivery of policies free canteen 5P is leaning more to the classical approach and human relations approach.